Analisis Penerapan Manajemen Strategi Pada PT. Bank BTPN Tbk Dalam Meningkatkan Loyalitas Nasabah - Aprilia, Tiffany (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study analyzes the implementation of strategic management at PT Bank BTPN Tbk in enhancing customer loyalty. The intense competition in the banking sector demands strong innovation and strategies to retain and attract customers. This study uses SWOT analysis to assess the bank's strengths and opportunities, focusing on digital transformation, especially through the Jenius platform. The data used comes from Bank BTPN’s annual reports over the last five years (2018-2023). The results indicate that digital innovation, operational efficiency improvement, and risk management are key factors in maintaining customer loyalty. Each implemented strategy, such as enhancing digital services during the pandemic, successfully increased customer loyalty significantly.